Antistatic polyester filament yarn and preparation method thereof
By using a core sheath structure in the polyester filament, using polyester slices as the core layer and anti-static masterbatch and carbon nanotube composite as the sheath layer, the problems of anti-static performance attenuation and mechanical performance reduction are solved, and efficient synergistic improvement of anti-static and mechanical performance is achieved.
Patent Information
- Application Number
- CN202510304363.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-06-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The antistatic properties of existing antistatic polyester filaments quickly attenuate during use, and the antistatic components reduce the mechanical properties of the fibers.
Anti-static polyester filaments with core sheath structure are made of polyester slices, and the sheath is made of anti-static masterbatch and carbon nanotube composite. Through special-shaped cross-section design and reasonable material ratio, effective separation and coordination of anti-static and mechanical properties can be achieved.
It effectively improves the mechanical strength and antistatic properties of polyester filaments, avoids the damage to the fiber structure by antistatic components, ensures the long-term stable performance of antistatic properties, and simplifies the process and reduces production costs.
Smart Images

Figure CN120138838A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of synthetic fibers, and particularly to an antistatic polyester filament and a preparation method thereof. Background Art
[0002] Polyester fiber, also known as polyester fiber, is a fiber obtained by spinning a polyester formed by polycondensation of organic dibasic acids and diols; and antistatic polyester filament is a polyester fiber with antistatic properties after being treated by a special process or material modification; antistatic polyester filament is a functional fiber based on polyester fiber, which has antistatic properties by adding antistatic agents, modified materials or adopting special spinning processes.
[0003] Currently, the following methods are mainly used in the market to endow polyester with antistatic function: 1. Blending antistatic method: mainly in the process of melt spinning, an antistatic agent is mixed with polyester raw materials, so that the antistatic agent is dispersed in the fiber, and a polar layer that can adsorb moisture in the air is formed on the fiber surface, thereby achieving antistatic; 2. Surface coating method: in the fiber spinning or post-finishing stage, spraying or dipping processes are used to form a coating containing an antistatic agent on the fiber surface to achieve antistatic effect; 3. Copolymerization modification method: by adding monomers with polar or conductive groups during the synthesis of polyester chips, the antistatic function is embedded in the polymer molecular chain to achieve a stable antistatic effect.
[0004] However, for antistatic polyester filaments produced by blending or surface coating methods, since antistatic agent molecules usually exist in the fiber in the form of physical adsorption or weak chemical bonds, after multiple washes or long-term friction, the antistatic molecules will volatilize or migrate, resulting in the loss of the original polar function on the fiber surface, thus unable to continuously adsorb moisture to reduce resistance, and ultimately leading to the attenuation of antistatic performance; at the same time, the antistatic agent or conductive material cannot be molecularly uniform in the fiber, which will cause significant differences in the conductive properties of different regions of the fiber, thereby reducing the overall antistatic effect.
[0005] Moreover, if the blending method is used, due to the large differences in the physical and chemical properties between the added antistatic agent or conductive material and the polyester matrix, this will damage the arrangement and crystal structure of the original polymer chain, resulting in a reduction in the mechanical properties of the fiber and making the fiber prone to breakage during use.
[0006] For the copolymerization modification method, its reaction conditions are relatively harsh, the process is complex and difficult, and the production cost is relatively high, making it difficult to be scaled up. Summary of the Invention
[0007] The present invention provides an antistatic polyester filament and a preparation method thereof, which solve the problem that the antistatic performance of the existing antistatic polyester filament rapidly decays during use, resulting in a reduction in the antistatic effect, and avoid the problem that the existing antistatic components reduce the mechanical properties of the polyester filament.
[0008] To achieve the above object, the technical solution adopted by the present invention is: an antistatic polyester filament, comprising a core layer and a sheath layer made by melt spinning, wherein the sheath layer wraps around the outer surface of the core layer; the core layer is made by melt spinning of polyester chips; the sheath layer is made by mixing an antistatic masterbatch and a carbon nanotube composite; wherein, the mass fraction of the polyester chips is 85-93%, the mass fraction of the antistatic masterbatch is 5-12%, and the mass fraction of the carbon nanotube composite is 2-3%.
[0009] The present invention is further provided that the carbon nanotube composite includes carbon nanotubes and a polydopamine layer wrapped on the surface of the carbon nanotubes.
[0010] The present invention is further provided that the core layer and the sheath layer adopt a special-shaped cross-section design, the cross-section of the sheath layer is in a "cross" shape, and the cross-section of the core layer is circular.
[0011] The present invention is further provided that the antistatic masterbatch is prepared by melt blending polyether ester amide, ionic liquid and titanate coupling agent.
[0012] The present invention is further provided that the ionic liquid includes 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, and its mass ratio to polyether ester amide is 1:2.
[0013] The present invention is further provided that in the antistatic masterbatch, the mass fraction of the polyether ester amide is 60-70%, the mass fraction of the ionic liquid is 20-30%, and the mass fraction of the titanate coupling agent is 5-10%.
[0014] The present invention is further provided that the antistatic masterbatch further includes sulfonated polyaniline, which is melt blended with polyether ester amide, ionic liquid and titanate coupling agent.
[0015] The present invention is further provided that the ionic liquid further includes epoxy silane mixed and reacted with 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide.
[0016] A preparation method of an antistatic polyester filament, which is used to prepare an antistatic polyester filament, includes the following steps: S1. Manufacture of antistatic masterbatch: Polyether ester amide, ionic liquid, sulfonated polyaniline and titanate coupling agent are melt blended by a twin-screw extruder, and then granulated to obtain an antistatic masterbatch; S2. Preparation of carbon nanotube composite: Mix carbon nanotubes with polydopamine, ensure the uniform dispersion of carbon nanotubes through ultrasonic treatment, and then react the two to form a coating film of polydopamine on the surface of carbon nanotubes to obtain a carbon nanotube composite; S3. Pretreatment before spinning: Dry the antistatic masterbatch prepared in S1 and the carbon nanotube composite prepared in S2 together with polyester chips until their moisture content is lower than 0.05%; S4. Melt spinning: Add the dried antistatic masterbatch and carbon nanotube composite in S3 into the sheath hopper of a bi-component spinning machine for mixing, add polyester chips into the core hopper of the bi-component spinning machine, and then carry out melt spinning. Through the spinneret of the spinning machine, filaments with a "cross-shaped" cross-section in the sheath layer and a circular cross-section in the core layer are produced; S5. Cooling and drawing: Cool the filaments produced in S4 in a water bath, then stretch them through a traction device, and finally shape them through a heat setting machine to obtain polyester fibers; S6. Rewinding: Rewind the polyester fibers in S5 through a rewinder, and set the rewinding speed to 1000 - 1500 m / min.
[0017] The present invention is further set as follows: During the melt spinning process of the spinning machine, the temperature is set at 280 - 300 °C, and the spinning speed is 500 - 800 m / min.
[0018] In summary, the beneficial effects of the present invention: Compared with the prior art, in the present application, the filaments adopt a core-sheath structure, where the core layer is made of polyester and the sheath layer is made of a mixture of an antistatic masterbatch and a carbon nanotube composite. Compared with the antistatic performance obtained by the prior art polyester filaments through blending or surface coating methods, the core-sheath structure realizes the effective separation and synergy of antistatic performance and mechanical properties. The core layer ensures the basic mechanical strength of the polyester filaments, while the sheath layer plays an antistatic function, avoiding the traditional antistatic agent from damaging the arrangement of polyester polymer chains and crystal structures, effectively improving the mechanical strength of the polyester filaments and solving the problem of their easy breakage.
[0019] At the same time, the combination of the antistatic masterbatch and the carbon nanotube composite in the sheath layer effectively improves the antistatic performance. Among them, the antistatic masterbatch uses a variety of high-performance antistatic components to act synergistically to form a stable and efficient conductive network in the sheath layer, thereby improving the antistatic performance of the polyester filaments; at the same time, the presence of the sheath layer provides a relatively closed and stable environment for these antistatic components, effectively reducing external factors such as washing and friction from eroding and damaging the antistatic components, effectively avoiding the rapid attenuation of the antistatic components during long-term use, and ensuring the long-term stable performance of the antistatic performance.
[0020] Moreover, the antistatic polyester filament in this application is prepared by the method of compounding melt spinning with an antistatic masterbatch. Compared with the copolymerization modification method, the process method is simpler, reducing the complexity and cost of production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the structural diagram of this application.
[0022] Figure 2 is the cross-sectional view of the polyester filament of this application.
[0023] Figure 3 is the process flow diagram of the preparation method of this application.
[0024] Reference numerals: 1, core layer; 2, sheath layer. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0025] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts fall within the scope of the present invention.
[0026] Embodiment 1
[0027] As Figure 1-2 shown, this embodiment discloses an antistatic polyester filament, including a core layer 1 made of melt spinning and a sheath layer 2, and the sheath layer 2 is wrapped around the outer surface of the core layer 1; the core layer 1 is made by melt spinning of polyester chips; the sheath layer 2 is made by mixing an antistatic masterbatch and a carbon nanotube composite.
[0028] Specifically, the polyester chips used in the core layer 1 itself have excellent polymer chain structures and crystallization properties, and can form highly oriented and closely arranged fiber structures during the melt spinning process, thereby endowing the core layer 1 with excellent mechanical strength and physical properties. Its high tensile strength, good wear resistance, and stable physical and chemical properties ensure that the filament can maintain a stable shape and performance in a complex and changing use environment, greatly extending the service life and application range of the filament; thus, it can ensure the basic strength and toughness of the fiber, providing a solid support for the overall structure; while the sheath layer 2 focuses on exerting the antistatic function, and the antistatic masterbatch and carbon nanotube composite in it can effectively conduct charges and reduce the accumulation of static electricity. Since the antistatic components are concentrated in the sheath layer 2, they avoid interfering with and damaging the arrangement of the polyester molecular chains and the crystal structure of the core layer 1, thereby maximizing the retention of the mechanical properties of the fiber and making it not prone to problems such as breakage during use.
[0029] At the same time, as Figure 1-2As shown in the figure, the core layer 1 and the sheath layer 2 adopt a special-shaped cross-section design. The cross-section of the sheath layer 2 is in a "cross" shape, and the cross-section of the core layer 1 is circular. The "cross" structure increases the surface area of the sheath layer 2, thereby increasing the contact opportunity between the antistatic component and the external charge, and improving the charge conduction efficiency. The circular cross-section of the core layer 1 can achieve a perfect structural match with the "cross"-shaped sheath layer 2 on the basis of ensuring uniform distribution of the internal mechanical strength, ensuring that the filament can evenly transfer the load when stressed, thereby improving the overall mechanical properties and anti-fatigue characteristics of the filament. Through mechanical property tests and antistatic property tests on filaments with different cross-sectional shapes, it is found that this core-sheath special-shaped cross-section design can achieve the optimal balance of mechanical properties and antistatic properties on the premise of minimizing the material usage.
[0030] Furthermore, the antistatic masterbatch in the sheath layer 2 is prepared by melt blending polyether ester amide, ionic liquid and titanate coupling agent.
[0031] Specifically, the polar groups of polyether ester amide can form hydrogen bonds or electrostatic interactions with antistatic agent molecules, thereby evenly dispersing the antistatic agent molecules in its matrix and preventing their agglomeration and migration during use. At the same time, the molecular chain contains ether bonds, ester bonds and amide bonds, which makes it have good flexibility and compatibility, and can be evenly and tightly mixed with other components to form a stable and continuous structure, thereby significantly improving the dispersion uniformity and long-term stability of the antistatic agent in the fiber.
[0032] For ionic liquids, such as 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, the anions and cations therein can move freely under the action of an electric field to conduct charges. When it is mixed with polyether ester amide, the ionic liquid forms a dense and efficient conductive channel in the sheath layer 2 under the dispersion of polyether ester amide, thereby greatly reducing the surface resistance of the filament and enhancing the antistatic effect. And, adding epoxy silane to the ionic liquid can chemically react with the active groups in the ionic liquid to form a more stable chemical structure, reducing the decomposition and volatilization of the ionic liquid during use, thereby ensuring its long-term effective conduction of electricity, enhancing the stability of the ionic liquid, enabling the stable ionic liquid to continuously and effectively build a conductive channel, so that the filament can maintain good antistatic performance under long-term use and various environmental conditions, and reduce the attenuation of the antistatic performance.
[0033] At the same time, it can improve the interfacial binding force between the ionic liquid and other components such as polyether ester amide, so that the ionic liquid can be more evenly dispersed in the antistatic masterbatch. The enhanced compatibility helps the ionic liquid to be more evenly distributed in the filament, avoiding too large local differences in antistatic performance, so that the overall antistatic effect of the filament is more uniform and reliable.
[0034] The molecular structure of titanate coupling agent contains both inorganic and organic groups, which can react chemically with the inorganic components of antistatic agent and the organic matrix of polyether ester amide respectively to form chemical bonds, thereby improving the interface compatibility and bonding force. Its addition to antistatic masterbatch can effectively improve the interface compatibility between the components in the antistatic masterbatch and enhance the chemical bonding force between them, thereby improving the adhesion between antistatic agent and polyester fiber, reducing the migration and volatilization of antistatic components during use, and enhancing the stability and durability of the antistatic performance of filament.
[0035] In addition, sulfonated polyaniline is added to the antistatic masterbatch. The sulfonic acid groups in the sulfonated polyaniline can combine with the TFSI⁻ anions in the ionic liquid through hydrogen bonds to form a continuous ion network, thereby inhibiting "ion aggregation failure" and improving the conductivity of polyester filaments in a dry environment. Specifically, sulfonated polyaniline and other components in the antistatic masterbatch, such as polyetheresteramide and ionic liquids, work together. Its molecules can fill in the tiny gaps in the conductive network formed by other components to form a more continuous and dense conductive network. In a dry environment, when static electricity is generated on the surface of the filament, sulfonated polyaniline can quickly participate in the conduction of the charge, quickly conduct away the static electricity, and avoid the accumulation of static electricity. At the same time, due to its own good chemical stability, sulfonated polyaniline is not prone to performance changes under dry conditions, thus providing a strong guarantee for the antistatic stability of the filament in a dry environment.
[0036] Furthermore, the carbon nanotube composite in the sheath 2 includes carbon nanotubes and a polydopamine layer wrapped on the surface of the carbon nanotubes; the carbon nanotubes, with their extraordinary conductivity and excellent mechanical strength, have brought a qualitative leap in the antistatic and mechanical properties of the filaments. The ingenious wrapping of the polydopamine layer not only greatly improves the uniformity of the dispersion of the carbon nanotubes in the sheath 2, but also enhances the chemical compatibility and physical binding force between the carbon nanotubes and other components through its rich functional groups. This synergistic effect allows the carbon nanotubes to be integrated into the sheath 2 structure like a fish in water, further improving the antistatic performance and overall mechanical stability of the filaments. Specifically, the functional groups of polydopamine can chemically react with the surface of the carbon nanotubes to form a tight bond of covalent bonding, and can also weave a network of hydrogen bonds or electrostatic interactions with other components in the sheath 2, thereby significantly improving the dispersion and compatibility of the carbon nanotubes.
[0037] In addition, in terms of material ratio, the ionic liquid includes 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide smoke, and the mass ratio of the ionic liquid to the polyetheresteramide is 1:2.
[0038] Specifically, the mass ratio of the ionic liquid to the polyether ester amide is set to 1:2. This ratio is designed to ensure an optimal balance among the antistatic performance, mechanical properties, and stability of the antistatic polyester filament. The polyether ester amide has polar groups that can form a stable chemical network with the ions in the ionic liquid through hydrogen bonding or electrostatic interactions, thereby creating conductive channels in the fiber. At a ratio of 1:2, the polyether ester amide can effectively disperse the ionic liquid in the fiber, ensuring the efficiency of the conductive channels and avoiding the instability caused by excessive ionic liquid. The ionic liquid can not only provide freely moving ions to assist in charge conduction but also maintain efficient antistatic performance in a low-humidity environment. The polyether ester amide forms a conductive water film through hygroscopic action to further enhance charge conduction. Therefore, a ratio of 1:2 can ensure the synergistic effect of the two, maintaining conductivity without affecting the mechanical properties of the fiber. If the ratio of the ionic liquid to the polyether ester amide is lower than 1:2, the amount of the ionic liquid will be insufficient, resulting in inefficient conductive channels and the possible failure to fully exhibit antistatic performance. Especially in a low-humidity environment, the insufficient number of free ions in the ionic liquid restricts charge conduction, thereby affecting the antistatic effect of the filament. If the ratio exceeds 1:2, excessive ionic liquid may lead to uneven distribution or even migration in the fiber, thus affecting the stability and durability of the fiber and possibly damaging the molecular structure of the polyether ester amide, causing the mechanical properties of the fiber to decline, becoming more fragile, and prone to breakage or performance degradation. Therefore, a mass ratio of 1:2 in the present invention can ensure the uniform distribution of the ionic liquid and the polyether ester amide in the fiber, while improving the conductive efficiency, extending the service life, and not compromising the mechanical strength of the fiber.
[0039] Furthermore, the mass fraction of the polyester chips is 85 - 93%; the proportion of the polyester chips is set between 85% and 93%. This proportion is mainly to ensure the basic mechanical strength and stability of the filament. The polyester chips themselves have excellent polymer chain structures and crystallization properties. During the melt spinning process, they can form a highly oriented and closely arranged fiber structure, endowing the core layer 1 with high tensile strength and wear resistance. This proportion can ensure the mechanical properties of the polyester and prevent the fiber from becoming fragile due to the addition of excessive functional components. If the mass fraction of the polyester chips is lower than 85%, the filament will lose sufficient strength and toughness and be prone to breakage or wear during use. If the proportion of the polyester chips exceeds 93%, it will inhibit the function of the functional components of the antistatic masterbatch, resulting in the failure to achieve the expected antistatic performance. Therefore, the proportion of the polyester chips within this range can ensure good functionality while guaranteeing mechanical properties.
[0040] The mass fraction of the antistatic masterbatch is 5 - 12%, mainly to provide sufficient antistatic performance and ensure its stability. The polyether ester amide in the masterbatch has polar groups, which can form hydrogen bonds or electrostatic interactions between the ionic liquid and the titanate coupling agent, thus uniformly dispersing the antistatic components in the fiber. This dispersion effect can effectively prevent the agglomeration or migration of the antistatic components, thereby maintaining the long-term stability of the fiber. The molecular chain structure of the polyether ester amide also has good flexibility and compatibility, which can ensure the uniform distribution of the antistatic components in the fiber and avoid local property differences caused by uneven distribution. If the mass fraction of the antistatic masterbatch is less than 5%, the antistatic performance cannot be fully exerted, resulting in a high surface resistance of the filament and the problem of electrostatic accumulation cannot be effectively suppressed; while if the mass fraction of the antistatic masterbatch exceeds 12%, it may affect the mechanical properties of the fiber, especially the tensile strength and flexibility, causing the fiber to become brittle and not suitable for various environmental conditions. Therefore, this ratio range can maintain excellent antistatic effects without damaging the mechanical properties.
[0041] The mass fraction of the carbon nanotube composite is 2 - 3%. This is to ensure the enhancement of the conductive performance while avoiding the negative effects caused by excessive carbon nanotubes. Carbon nanotubes are a kind of highly conductive material that can provide additional conductive paths for the filament, enabling charges to be conducted quickly. The polydopamine coated on the surface of the carbon nanotubes can not only prevent the agglomeration of carbon nanotubes but also enhance their dispersion in the fiber by forming chemical bonding forces with other components. This enables the carbon nanotubes to form a stable and uniform conductive network in the fiber, improving the overall conductivity and antistatic performance of the filament. If the mass fraction of the carbon nanotubes is less than 2%, the number of conductive paths is insufficient, and the antistatic performance of the filament cannot reach the expected effect; while if the proportion of the carbon nanotubes exceeds 3%, it may lead to the agglomeration of carbon nanotubes, reducing their uniformity in the fiber, thereby affecting the conductive performance and may also cause an increase in the rigidity of the fiber, affecting its flexibility and applicability. Therefore, within the ratio range of 2 - 3%, the carbon nanotube composite can fully exert its conductivity while avoiding negative impacts on the fiber properties.
[0042] In the antistatic masterbatch, the mass fraction of polyether ester amide is 60 - 70%. As the matrix material of the masterbatch, the mass fraction of polyether ester amide is set between 60 - 70%. Polyether ester amide has polar groups that can form hydrogen bonds or electrostatic interactions with ions in the ionic liquid, thereby uniformly dispersing the antistatic components in the fiber, which is crucial for ensuring antistatic performance. The high flexibility and good compatibility of polyether ester amide enable it to form a stable structure with other components such as ionic liquid and titanate coupling agent, providing good mechanical properties. If the mass fraction of polyether ester amide is less than 60%, the antistatic components may not be fully dispersed, resulting in unstable antistatic effects, especially its stability will be affected under different environmental conditions; if the mass fraction of polyether ester amide exceeds 70%, it may inhibit the functions of ionic liquid and other functional components, causing insufficient antistatic performance of the filament. At the same time, too much polyether ester amide will affect the flexibility and adaptability of the fiber, reducing its mechanical properties. Therefore, a mass fraction of 60 - 70% of polyether ester amide ensures that the masterbatch can effectively play an antistatic role while providing strength.
[0043] The mass fraction of the ionic liquid is 20 - 30%. The ionic liquid is an excellent conductive material that can provide a conductive channel through freely moving ions, reduce the surface resistance, and enhance the antistatic effect. When the mass fraction of the ionic liquid is less than 20%, the conductive effect will be significantly reduced. Especially in a dry environment, the charge conduction ability will not meet the actual application requirements, resulting in the inability to continuously exert antistatic performance; while if the proportion of the ionic liquid exceeds 30%, it may lead to uneven distribution in the fiber, and even phenomena such as migration or volatilization, affecting the stability and durability of the filament, and ultimately resulting in the attenuation of the antistatic effect. Therefore, a mass fraction of 20 - 30% of the ionic liquid ensures that the ionic liquid can be evenly distributed in the fiber, play a lasting conductive role, and at the same time avoid stability problems caused by excessive amounts.
[0044] The mass fraction of the titanate coupling agent is 5 - 10%. Through the inorganic - affinity group and organic - affinity group in its molecular structure, the titanate coupling agent can chemically react with the inorganic substances in the antistatic components and the organic matrix of polyether ester amide respectively to form chemical bonding, thereby enhancing the binding force between the components and improving the dispersibility of the antistatic masterbatch. When the proportion of the titanate coupling agent is less than 5%, the binding force between the antistatic components may be insufficient, affecting the stability of the antistatic effect; if the proportion exceeds 10%, the filament may become too hardened, reducing its flexibility and even affecting the mechanical properties. Therefore, a proportion of 5 - 10% of the titanate coupling agent can ensure good compatibility and binding force between the components, enabling the filament to maintain good mechanical properties and stable antistatic performance under different environmental conditions.
[0045] In summary, the mixing ratio ranges of polyether ester amide, ionic liquid and titanate coupling agent are reasonable, which can achieve the best balance among mechanical properties, antistatic effect and long-term stability, ensuring excellent performance of the filament during use. If deviating from this range, the performance of each component may not be fully exerted, thus affecting the comprehensive performance of the antistatic polyester filament.
[0046] Meanwhile, in order to better analyze the antistatic performance and durability of the antistatic polyester filament, the following experiments were carried out in this application and the experimental schemes were given: Antistatic performance test Surface resistance test: According to the standard ASTM D257-99, using a high-precision digital ultra-high resistance micro-current measuring instrument, under the environmental conditions of a temperature of 23±2°C and a relative humidity of 50±5%, the antistatic polyester filament samples of the present invention and the existing antistatic polyester filament comparative samples were measured. Among them, at least 5 samples of each type were used for surface resistance measurement. During the measurement, 5 points were selected at different positions of the sample for measurement, and the average value was taken as the final surface resistance value.
[0047] Static decay performance test: According to the standard IEC61340-5-1:2016, using a static decay tester, under the condition of applying an initial voltage of 10 kV, the time required for the static electricity of the sample to decay to 10% of the initial voltage was measured. Similarly, each sample was tested 5 times and the average value was taken.
[0048] Durability test Washing durability test: According to the standard AATCC61-2013, the samples were simulatedly washed using an industrial washing machine. The washing program was set at a water temperature of 40°C, normal stirring intensity, and a standard detergent was used. After washing 5, 10, and 20 times, the samples were taken out respectively for surface resistance and static decay performance tests.
[0049] Friction durability test: According to the standard ASTM D4966-17, using a Martindale abrasion tester, under a pressure of 9 kPa, the samples were subjected to friction tests. The number of friction times was set at 100, 300, 500, and 1000 times respectively, and the surface resistance and static decay performance tests were carried out after each friction.
[0050] Through the above implementation schemes, the following experimental data were obtained: Test item The antistatic polyester filament of the present invention The antistatic polyester filament by blending method Initial surface resistance (Ω) 8.5×10^6 5.0×10^7 Initial static decay time (s) 0.5 2.0 Surface resistance after 5 washes (Ω) 9.2×10^6 1.0×10^8 Static decay time after 5 washes (s) 0.6 3.5 Surface resistance after 10 washes (Ω) 1.0×10^7 2.0×10^8 Static decay time after 10 washes (s) 0.7 5.0 Surface resistance after 20 washes (Ω) 1.2×10^7 3.5×10^8 Static decay time after 20 washes (s) 0.8 7.0 Surface resistance after 100 rubs (Ω) 9.8×10^6 1.5×10^8 Static decay time after 100 rubs (s) 0.6 4.0 Surface resistance after 300 rubs (Ω) 1.1×10^7 2.5×10^8 Static decay time after 300 rubs (s) 0.7 6.0 Surface resistance after 500 rubs (Ω) 1.3×10^7 4.0×10^8 Static decay time after 500 rubs (s) 0.8 8.0 Surface resistance after 1000 rubs (Ω) 1.5×10^7 6.0×10^8 Static decay time after 1000 rubs (s) 1.0 10.0 Surface resistance in dry environment (Ω) 7.5×10^6 4.5×10^7 It can be seen from the above experimental data that: Initial performance: The initial surface resistance of the antistatic polyester filament of the present invention is 8.5×10^6 Ω, and the static decay time is 0.5 s, showing good initial antistatic performance.
[0051] The initial surface resistance of the antistatic polyester filament prepared by the blending method is 5.0×10^7Ω, and the electrostatic decay time is 2.0s. Its initial antistatic performance is significantly weaker than that of the present invention.
[0052] Washing durability: As the number of washing times increases, the surface resistance and electrostatic decay time of the antistatic polyester filament of the present invention change relatively little. For example, after 20 washes, the surface resistance only rises to 1.2×10^7Ω, and the electrostatic decay time is 0.8s.
[0053] In contrast, the antistatic performance of the antistatic polyester filament prepared by the blending method drops significantly after washing. After 20 washes, the surface resistance is as high as 3.5×10^8Ω, and the electrostatic decay time extends to 7.0s.
[0054] Friction durability: After being rubbed multiple times, the antistatic polyester filament of the present invention can still maintain good antistatic performance. For example, after 1000 rubs, the surface resistance is 1.5×10^7Ω, and the electrostatic decay time is 1.0s.
[0055] The antistatic performance of the antistatic polyester filament prepared by the blending method deteriorates sharply under friction. After 1000 rubs, the surface resistance reaches 6.0×10^8Ω, and the electrostatic decay time is as long as 10.0s.
[0056] Dry environment: In a dry environment, the surface resistance of the antistatic polyester filament of the present invention is 7.5×10^6Ω, significantly lower than 4.5×10^7Ω of the antistatic polyester filament prepared by the blending method, indicating that the present invention still has better antistatic performance under dry conditions.
[0057] In summary, compared with the antistatic polyester filament prepared by the blending method, the antistatic polyester filament of the present invention shows significant advantages in terms of initial performance, washing durability, friction durability, and antistatic performance in a dry environment, and has better antistatic stability and persistence.
[0058] Example 2 To prepare an antistatic polyester filament as in Example 1, Example 2 provides a preparation method for an antistatic polyester filament, as Figure 3 shown, including the following steps: S1. Manufacturing of antistatic masterbatch: Polyether ester amide, ionic liquid, sulfonated polyaniline, and titanate coupling agent are melt-blended through a twin-screw extruder and then pelletized to obtain the antistatic masterbatch; Specifically, the temperature of the twin-screw extruder is set at 230°C - 250°C. This temperature range can ensure that all components are completely melted and evenly mixed. When the temperature is lower than 230°C, it may lead to insufficient melting of the material, poor dispersibility, and affect the stability of the masterbatch; when the temperature exceeds 250°C, it may cause some heat-sensitive components, such as ionic liquids, to decompose, resulting in a decrease in the antistatic effect.
[0059] The rotation speed of the screw can be set at 200 - 300 rpm to ensure sufficient mixing and plasticization of the material in the screw. If the rotation speed is too low, the material will not be evenly mixed, resulting in poor dispersibility of the masterbatch; if the rotation speed is too high, it may lead to too high a temperature, affecting the stability of the material.
[0060] For the extrusion pressure of the extruder, it can be set at 15 - 20 MPa. This pressure can ensure that the material evenly forms masterbatch during extrusion, avoiding the generation of bubbles or uneven distribution.
[0061] Through melt blending by a twin-screw extruder and pelletizing to form an antistatic masterbatch, it ensures that the components are evenly and stably dispersed in the masterbatch. This melt blending technology can reduce the stress of the material, making the antistatic masterbatch have good fluidity and uniformity, and further ensuring the conductivity of polyester filaments in subsequent processes.
[0062] Among them, before melt blending, epoxy silane can be added to the ionic liquid. Specifically, first add the ionic liquid to a dry and oxygen-free three-necked flask, then stir the ionic liquid, and slowly dropwise add γ-glycidoxypropyltrimethoxysilane. After the addition is complete, continue to stir the mixture with a magnetic stirrer under nitrogen protection. The stirring speed is moderate, and the stirring time is 2 - 4 hours to ensure sufficient mixing and reaction. Then an ionic liquid mixed with epoxy silane is obtained.
[0063] Among them, epoxy silane can be covalently bonded to the imidazole ring in the ionic liquid. Covalent bonding makes the migration rate of the ionic liquid very low at 80°C, lower than 2%. This means that during the use and processing of polyester filaments, the ionic liquid can stably exist in its position, is not prone to migration and loss, and thus can effectively play its roles of improving conductivity and enhancing antistatic performance for a long time.
[0064] S2. Prepare carbon nanotube composite: Mix carbon nanotubes with polydopamine, ensure the uniform dispersion of carbon nanotubes through ultrasonic treatment, and then react the two to form a coating film of polydopamine on the surface of the carbon nanotubes to obtain a carbon nanotube composite; Specifically, in this step, a carbon nanotube and polydopamine are mixed using an ultrasonic treatment device, and a chemical reaction is used to form a coating film of polydopamine on the surface of the carbon nanotube, thereby obtaining a carbon nanotube composite. Among them, the ultrasonic device vibrates through high-frequency sound waves to evenly disperse the carbon nanotubes in the solvent and avoid agglomeration. The ultrasonic device can be an ultrasonic cleaner, and its power can be set at 200 - 300 w. This power can effectively generate sufficient sound wave vibrations in the solution to ensure the uniform dispersion of the carbon nanotubes. The frequency can be set at 40 kHz. This frequency can ensure that the vibration of the ultrasonic wave is delicate enough to avoid damage to the carbon nanotube structure and ensure its uniform dispersion in the solution. The treatment time is set at 30 - 60 minutes. This time can ensure that the polydopamine completely forms a coating film on the surface of the carbon nanotube. Too short a time may result in incomplete coating and affect the conductivity.
[0065] Through ultrasonic treatment, it is ensured that the carbon nanotubes are fully dispersed in the solution, avoiding the phenomenon of agglomeration. The good dispersion of the carbon nanotubes helps to form a uniform conductive channel in the subsequent spinning and enhance the antistatic effect.
[0066] S3. Pretreatment before spinning: The antistatic masterbatch prepared in S1 and the carbon nanotube composite prepared in S2 are dried with polyester chips until their moisture content is lower than 0.05%, thereby ensuring that during the subsequent melt spinning process, moisture will not have an adverse effect on the quality of the fibers.
[0067] Among them, drying is carried out using a dryer. Through the dryer, the antistatic masterbatch and the carbon nanotube composite can remove moisture at a drying temperature of 70 - 80 °C, while avoiding damage to the antistatic components caused by high temperatures. If the temperature is too low (below 70 °C), it will cause incomplete removal of moisture and affect the subsequent melt spinning; if the temperature exceeds 80 °C, it may cause thermal decomposition of some components and affect the antistatic performance.
[0068] S4. Melt spinning: The dried antistatic masterbatch and carbon nanotube composite in S3 are added to the sheath layer 2 hopper of a bi-component spinning machine for mixing, and the polyester chips are added to the core layer 1 hopper of the bi-component spinning machine, and then melt spinning is carried out. A filament with a "cross-shaped" cross-section in the sheath layer 2 and a circular cross-section in the core layer 1 is produced through the spinneret of the spinning machine.
[0069] The bi-component spinning machine can simultaneously provide two independent spinning channels, and send the polyester chips and the antistatic masterbatch / carbon nanotube composite into the spinnerets of the core layer 1 and the sheath layer 2 respectively. This device ensures the simultaneous formation of fibers from two different materials by precisely controlling the temperature and flow rate. Among them, the temperature of the spinning machine is set at 280 - 300 °C, and the spinning speed is 500 - 800 m / min.
[0070] At this melting temperature, it can ensure that the polyester chips and the antistatic masterbatch can be fully melted, avoiding incomplete melting of the materials due to too low temperature, which will affect the strength of the fiber; too high temperature may cause material decomposition. And this spinning speed can ensure uniform stretching of the fiber during the forming process, avoiding the appearance of irregular structures or uneven stretching.
[0071] S5. Cooling and drawing: The filaments produced in S4 are cooled by a water bath cooling system, so that cold water can quickly cool the filaments just coming out of the melt spinning machine to ensure the stability of the fiber structure. Among them, the cooling water temperature can be set at 20 - 30 °C. Too high temperature may cause the fiber to be deformed by heat, and too low temperature may cause the fiber to cool too quickly, affecting its elasticity.
[0072] Then the cooled filaments can be drawn through a drawing device, and the draw ratio of the drawing device is set to 3:1 to 4:1. This drawing ratio can ensure that the fiber has appropriate strength and elongation. Too low draw ratio will cause the fiber to be uneven, affecting the final performance; too high draw ratio will cause the fiber to be too thin and easy to break.
[0073] Finally, the polyester fiber is obtained through a heat setting machine.
[0074] S6. Winding: The polyester fiber in S5 is wound through a winding machine, and the winding speed is set to 1000 - 1500 m / min. This speed can ensure the neat winding of the fiber and ensure that the fiber is not subjected to excessive tension during the winding process, avoiding breakage.
[0075] The above are only the preferred embodiments of the present invention and are not used to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the design concept of the present invention shall be included within the protection scope of the present invention.
Claims
1. An antistatic polyester filament, characterized in that: The invention comprises a core layer (1) and a sheath layer (2) made by melt spinning, wherein the sheath layer (2) is wrapped around the outer surface of the core layer (1); the core layer (1) is made by melt spinning of polyester chips; the sheath layer (2) is made by mixing antistatic masterbatch and carbon nanotube composite; wherein the mass fraction of the polyester chips is 85-93%, the mass fraction of the antistatic masterbatch is 5-12%, and the mass fraction of the carbon nanotube composite is 2-3%.
2. The antistatic polyester filament according to claim 1, characterized in that: The carbon nanotube composite comprises carbon nanotubes and a polydopamine layer wrapped on the surface of the carbon nanotubes.
3. The antistatic polyester filament according to claim 1, characterized in that: The core layer (1) and the sheath layer (2) are designed with special-shaped cross sections; the cross section of the sheath layer (2) is in a "cross shape" and the cross section of the core layer (1) is in a circular shape.
4. The antistatic polyester filament according to claim 1, characterized in that: The antistatic masterbatch is prepared by melt blending polyether ester amide, ionic liquid and titanate coupling agent.
5. The antistatic polyester filament according to claim 4, characterized in that: The ionic liquid includes 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide fume, and the mass ratio of the ionic liquid to the polyether ester amide is 1:
2.
6. The antistatic polyester filament according to claim 4, characterized in that: In the antistatic masterbatch, the mass fraction of the polyether ester amide is 60-70%, the mass fraction of the ionic liquid is 20-30%, and the mass fraction of the titanate coupling agent is 5-10%.
7. The antistatic polyester filament according to claim 4, characterized in that: The antistatic masterbatch also includes sulfonated polyaniline, which is melt-blended with polyether ester amide, ionic liquid and titanate coupling agent.
8. The antistatic polyester filament according to claim 5, characterized in that: The ionic liquid also includes epoxy silane which is mixed with 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide smoke.
9. A method for preparing an antistatic polyester filament, which is used to prepare an antistatic polyester filament as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Antistatic masterbatch manufacturing: polyether ester amide, ionic liquid, sulfonated polyaniline and titanate coupling agent are melt-blended by a twin-screw extruder, and then granulated to obtain antistatic masterbatch; S2. preparing a carbon nanotube composite: mixing carbon nanotubes with polydopamine, ensuring uniform dispersion of the carbon nanotubes by ultrasonic treatment, and then reacting the two to allow the polydopamine to form a coating film on the surface of the carbon nanotubes to obtain a carbon nanotube composite; S3, pre-spinning treatment: drying the antistatic masterbatch prepared in S1 and the carbon nanotube composite prepared in S2 with the polyester chips until the moisture content is less than 0.05%; S4, melt spinning: adding the antistatic masterbatch and carbon nanotube composite dried in S3 to the sheath layer (2) hopper of the two-component spinning machine for mixing, adding the polyester slices to the core layer (1) hopper of the two-component spinning machine, and then melt spinning, and producing filaments with a "cross-shaped" cross section of the sheath layer (2) and a circular cross section of the core layer (1) through the spinning head of the spinning machine; S5, cooling and drawing: cooling the filaments produced in S4 in a water bath, then stretching them through a traction device, and finally setting them through a heat setting machine to obtain polyester fibers; S6, winding: The polyester fiber in S5 is wound by a winding machine, and the winding speed is set to 1000-1500m / min.
10. The method for preparing antistatic polyester filament according to claim 9, characterized in that: During the melt spinning process, the temperature of the spinning machine is set at 280-300° C., and the spinning speed is 500-800 m / min.
Citation Information
Cited By
Aramid rope core conveying belt and preparation method and application thereof
CN121778362A
Aramid cord conveyor belt and its preparation method and application
CN121778362B